Pengaruh siklus hidup perusahaan terhadap penghindaran pajak dengan manajemen laba sebagai variabel intervening - Trie Lestari; Eddy Suranta; Pratana Puspa Midiastuty; Fachruzzaman Fachruzzaman (Jurnal Akuntansi, Keuangan, dan Manajemen, 2020)
Purpose: This study aims to empirically prove the influence of the company’s life cycle on tax avoidance with earnings management as an intervening variable. Research methodology: Tax avoidance used ETR proxies and firm life cycle was proxied using an average sales growth of 5 years. The firm life cycle used the Dummy variable, valued at 1 classified growth stage and valued at 0 mature stages. Study sample of non-financial companies listed on the Indonesia Stock Exchange in 2010-2018. The sample selection method is Purposive Sampling method with 668 observations. Data analysis method with multiple regression analysis. Results: The firm life cycle has an influence on tax avoidance, indicating companies that are in a mature life cycle will avoid lower taxes than companies that are in the growth stage. Regression results indicate that earnings management variable is a partial intervening/mediation variable (Partial Mediation), which indicates that the firm life cycle influences tax avoidance through earnings management. Limitations: The limitation of this study is that the firm life cycle variables studied were only two cycles. In addition, the limitation of this study is that it only uses proxies for average sales growth to classify the life cycles of sample companies. Contribution: To add references related to tax avoidance, firm’s life cycle and earnings management. Suggestions for further research are adding other cycles so that they can more broadly see the effect of the firm’s life cycle on tax avoidance. And use other proxies that are more representative in classifying the firm’s life cycle, such as using based on cash flow patterns. Keywords: Tax avoidance, Firm life cycle, Earnings management